Strategi Bisnis Internasional Untuk Menghadapi Tantangan Ekonomi dan Politik di Tahun 2024 - Suci Andini Kesuma; Hendra Ibrahim (Journal of Islamic Economics and Finance, 2024)
The year 2024 will be a year full of economic and political challenges for companies operating in international markets. Some of the factors that may affect international business are the Covid-19 pandemic, climate change, geopolitical tensions, trade protectionism, and digital transformation. This article aims to identify and analyze international business strategies that can help companies face these challenges. The strategies discussed include strategic alliances, product diversification, segmented digital marketing, flexible pricing adjustments, and international human resource management. The article also provides examples of companies that have successfully implemented these strategies in various markets. This article is expected to provide insights and inspiration for business people who want to improve their performance and competitiveness in the international market